2010 Annual International Conference of the IEEE Engineering in Medicine and Biology 2010
DOI: 10.1109/iembs.2010.5627789
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic and metabolic effects of OSA in childhood obesity

Abstract: This study investigates the effects of exposure to intermittent hypoxia on cardiovascular autonomic control and metabolic function in obese children with obstructive sleep apnea (OSA). Each subject underwent: (1) a polysomnography; (2) morning fasting blood samples and a subsequent FSIVGTT; (3) noninvasive measurement of respiration, arterial blood pressure, and heart rate during supine and standing postures. Assessment of adiposity was performed using a DEXA scan. From these measurements, we deduced the perti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…4,5,15,16 This study investigated whether DEXA scans could be used to show that a sensitive measure of fat mass and distribution of fat correlates with SRBD in obese/ overweight pediatric patients. We found that total body fat mass and trunk fat mass as measured on DEXA scanning, as well as BMI, were associated with total arousal index and desaturation index.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,5,15,16 This study investigated whether DEXA scans could be used to show that a sensitive measure of fat mass and distribution of fat correlates with SRBD in obese/ overweight pediatric patients. We found that total body fat mass and trunk fat mass as measured on DEXA scanning, as well as BMI, were associated with total arousal index and desaturation index.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 In the pediatric age group, it has been associated with signifi cant metabolic and autonomic dysfunction. [3][4][5] In children obesity has been shown to be an independent risk factor for snoring and obstructive sleep apnea (OSA). 6,7 The literature also provides evidence regarding the predictors of SRBD in obese children.…”
mentioning
confidence: 99%
“…In addition, Snow et al (2010) also showed a higher gene expression among genes that are involved in the synthesis and transport of catecholamines, as well as in selected important receptors, with such findings suggesting the presence of increased bioavailability of catecholamines. More recently, several groups have confirmed that AHI is a significant independent predictor of noradrenaline and adrenaline levels (Kelly et al, 2010; Oliveira et al, 2010; O’Driscoll et al, 2011). In a different study, Nakra et al (2008) assessed a small group of obese children and adolescents in whom norepinephrine levels were assessed hourly throughout the night before and after treatment with CPAP for 3 months.…”
Section: Autonomic Alterations In Children With Osamentioning
confidence: 94%
“…Since OSA is strongly connected to autonomic dysfunction, the potential contribution of autonomic alterations to metabolic morbidities in the context of OSA can not be ignored (Trombetta et al, 2010; Spiegel et al, 2004). The extent of such connection in children has however not been as thoroughly explored as it should (Oliveira et al, 2010). Indeed, a substantial number of studies has suggested the presence of significant associations between the spectrum of sleep disordered breathing in children and insulin resistance and alterations in lipid homeostasis (Alexopoulos et al, 2011; Canapari et al, 2011; Deboer et al, 2012; Hannon et al, 2011; Nakra et al, 2008; Tauman et al, 2005; Tsaoussoglou et al, 2010; Verhulst et al, 2009; Waters et al, 2007).…”
Section: Autonomic Nervous System Alterations In Children With Osamentioning
confidence: 99%